The Influence of Comic Media on Students' Concept Understanding on Chemical Bonding Materials - Sinta, Ida Norma; Wardani, Sri; Kurniawan, Cepi (International Journal of Active Learning, 2021)
Research is motivated by the lack of understanding of students on chemical bonding material so that it has an impact on low learning outcomes and the use of effective learning media has not been utilized optimally. This study aims to determine the effect of comic media on students' understanding of concepts. This research is a mixed method. The research subjects of SMA Muhammadiyah 1 Sumenep class X IPA I and II were 39 students divided into 25 males and 14 females. Research data obtained and analyzed. The results showed that the average level of concept understanding with pretest and posttest was 12.09% and 69.6%, the percentage increase was 57.51%, the pretest normality test was 0.513 (> 0.05), then the data was normal, while the posttest was 0.368 (> 0.05) then the data is normal. The t-test results of the pretest and posttest are the tcount value (27,042)> ttable (1,686). The ttable value obtained with a confidence level of 95% and df 38, so it can be concluded that there is an effect of using comics media on the understanding of the concepts of Sumenep Private High School students on chemical bonds.